Factors Influencing The Welfare Of Rubber Farmers (Hevea Brasilliensis) - Leovita, Angelia; Deperiky, Deded; Dona, Okta Mitra (JURNAL AGRIBISAINS, 2025)
Kamang Baru District, Sijunjung Regency is one of the rubber producing areas with the largest land area in West Sumatra and within a period of 5 years there has been a decline in rubber prices reaching 33.33 percent, which has an impact on farmers' income and affects their welfare. This study aims to 1) Describe the characteristics of rubber farmers. 2) Analyze the level of welfare of rubber farmers. 3) What factors affect the welfare of rubber farmers. The analytical tools used are Qualitative Descriptive Analysis, criteria according to Gilarso and Multiple Linear Regression Analysis. These results show that the majority of farmers are male, aged 54–57 years, have farming experience of over 25 years, are elementary school graduates, have a land area of ​​0.25–0.54 ha, have family dependents of 2–5 people, and receive Rp 1,666,000 – Rp 2,814,000 per month. Most farmers are in the medium welfare category, namely 72.72 percent. The variables of rubber farming period (X4), rubber production (X5), land area (X6), price (X7), capital (X8), income (X9) have a significant effect on farmer welfare, while age (X1), education level (X2), number of family dependents (X3), and government policy (X10) do not have a significant effect on farmer welfare. Steps are needed from the government and related agencies to improve farmer welfare through increased production which can be done through plant rejuvenation, technical cultivation extension, access to quality inputs.